10.8k views
4 votes
Please please please help me and explain how you did it!!

Please please please help me and explain how you did it!!-example-1
User Rui Nunes
by
4.9k points

2 Answers

3 votes

Answer:

The third option: -24

Explanation:

21 +
6^(2) - ( 35 - 8 ) · 3

So you need to solve this according to BEDMAS / PEMDAS (same thing)

Brackets/Parentheses, Exponents, Division/Multiplication, Addition/Subtraction.

Btw, don't worry about ( · ), it means multiplication ( × )

So according to BEDMAS / PEMDAS...

= 21 +
6^(2) - ( 35 - 8 ) · 3

= 21 +
6^(2) - 27 · 3

= 21 + 36 - 27 · 3

= 21 + 36 - 81

= 57 - 81

= -24

User Robert Knight
by
5.3k points
5 votes

Answer:

21+6²-(35-8).3

= 21+36-27*3

= 21+36-81

= 57-81

= -24

User Scoutman
by
4.4k points